INTEGRASI PRINSIP KEBERLANJUTAN DALAM SUPPLY CHAIN UNTUK MENINGKATKAN EFISIENSI DAN MENGURANGI DAMPAK LINGKUNGAN DI PABRIK TAHU - Santika, Nilam; Ramadhani, Noviana; Yuwandono, Rr Jihan Faadhilah; Pandin, Maria Yovita R. (STIE DWI SAKTI BATURAJA, 2024)
This research focuses on the implementation of Green Supply Chain Management (GSCM) in the tofu industry in Bohar, Sidoarjo, with the aim of increasing efficiency and reducing environmental impacts. The research method used is a qualitative approach through interviews and direct observation in the field. The results showed that the tofu factory in Bohar has implemented GSCM practices, including pollution prevention, product management, and sustainable development. One example is the utilization of solid waste as animal feed and the treatment of liquid waste using a wastewater treatment plant (WWTP), which has a positive impact on the environment. However, challenges such as efficient water use management still need to be addressed. Recommendations from this study include the importance of innovation and collaboration with stakeholders to improve the sustainability of the tofu industry in the area.